2007
DOI: 10.1007/s10832-007-9106-6
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature synthesis of barium titanate thin films by nanoparticles electrophoretic deposition

Abstract: The nanoparticles electrophoretic deposition (EPD) of barium titanate (BaTiO 3 or BTO) thin films was investigated. BTO nanocrystallites in a pseudocubic perovskite phase with an average particle size of about 10 nm were synthesized at a low temperature of 90°C by a highconcentration sol-gel process. By using a mixed solvent of 2-methoxyethanol and acetylacetone as dispersing medium, transparent and well-dispersed BTO nanocrystallites suspensions within the concentration range of 0.0125 to 0.20 mol/l was succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For example, Xiong et al [10] and Winkleman et al [11] attested that the micrometer and nanometer scaled micropatterns were electrophoretically achieved by selective deposition of the spherical latex particles in the predesigned trenches, respectively. In our lab, Dr. Wu et al [3,4] also proved previously that electron beam lithography and EPD could be combined and employed for selective deposition of nanoscale BaTiO 3 micropatterns with the microarrays of lines, grids, and dots. On the other hand, it has been demonstrated that an important challenge in micromanufacturing is the direct growth or assembly of nanoelements over macroscopic length scales [12].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, Xiong et al [10] and Winkleman et al [11] attested that the micrometer and nanometer scaled micropatterns were electrophoretically achieved by selective deposition of the spherical latex particles in the predesigned trenches, respectively. In our lab, Dr. Wu et al [3,4] also proved previously that electron beam lithography and EPD could be combined and employed for selective deposition of nanoscale BaTiO 3 micropatterns with the microarrays of lines, grids, and dots. On the other hand, it has been demonstrated that an important challenge in micromanufacturing is the direct growth or assembly of nanoelements over macroscopic length scales [12].…”
Section: Introductionmentioning
confidence: 65%
“…In particular, the technique for fabricating patterned colloidal microstructures from particle suspensions has the promising purposes in the materials processing [2]. Very recently, a great deal of attention has been focused on the fabrication of patterned electroceramic materials due to the increasing demands for integrating them into microelectronic devices, and their potential applications as sensing, optical, and photonic band-gap materials [3,4]. Specially, deposition of micropatterned barium titanate (BaTiO 3 ) films onto metal electrodes has attracted significant interest for its conspicuous technological applications in both the electronic and optical component industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation